2021
DOI: 10.3390/su13137512
|View full text |Cite
|
Sign up to set email alerts
|

School Refusal Behaviour Profiles and Academic Self-Attributions in Language and Literature

Abstract: School refusal behaviour has a major impact on the lives of children and adolescents, seriously affecting their personal, academic and social adjustment. The objectives of this research were: (1) to identify, using latent profile analysis, school refusal behaviour profiles based on the functional model and (2) to analyse the relationship between the identified school refusal behaviour profiles and academic self-attributions in language and literature. The School Refusal Assessment Scale-Revised (SRAS-R) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
11
0
3
Order By: Relevance
“…The coefficients of internal consistency in this study were 0.72, 0.75, 0.71, and 0.69, respectively, for each of the four factors. Prior studies carried out with Spanish (Gonzálvez et al, 2021), German (Walter et al, 2017) and North American (Haight et al, 2011) have shown the suitability and applicability of this instrument in adolescent population.…”
Section: Instrumentsmentioning
confidence: 91%
“…The coefficients of internal consistency in this study were 0.72, 0.75, 0.71, and 0.69, respectively, for each of the four factors. Prior studies carried out with Spanish (Gonzálvez et al, 2021), German (Walter et al, 2017) and North American (Haight et al, 2011) have shown the suitability and applicability of this instrument in adolescent population.…”
Section: Instrumentsmentioning
confidence: 91%
“…In respect of the profile solutions, these works coincide in finding a group characterized by low levels of ANA, ESE, PAS, and PTR, which has been predominantly called non-SRB. Five in eight studies identified a mixed profile with high levels of explanatory factors based on both negative reinforcement (ANA and ESE) and positive reinforcement (PAS) (Giménez-Miralles, Gonzálvez, Sanmartín et al, 2021;Gonzálvez, Kearney et al, 2018). The mixed profile has been named anxious SRB, since previous studies found that school refusers whose causes of the ongoing SRB are the first three SRAS-R dimensions tended to show high levels of anxious symptoms (e.g., Fernández-Sogorb et al, 2018;Gonzálvez, Inglés, Fernández-Sogorb et al, 2020).…”
Section: School Refusal Behavior In Adolescencementioning
confidence: 99%
“…The anxious and high SRB groups are considered risk profiles, because they have proved to be related to low self-concept , high levels of psychopathological symptoms such as depression or anxiety Gonzálvez, Kearney et al, 2018), and family conflicts . Regarding the academic field, it was found that Spanish adolescents with an anxious SRB profile showed low scores in learning strategies, motivation towards learning being one of the variables examined (Giménez-Miralles, Gonzálvez, Sanmartín et al, 2021). Nevertheless, empirical evidence on the relationship between academic motivation and SRB profiles remains scarce.…”
Section: School Refusal Behavior In Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…At an analytic level, dimensional clinical profiles may be useful for informing broad categories. Gonzálvez and colleagues have been a leader in this approach, having investigated numerous clinical profiles of school attendance problems based on social and school anxiety, self-efficacy, self-esteem, and negative affect, among other variables (e.g., Gonzálvez et al, 2019bGonzálvez et al, , 2020Gonzálvez et al, , 2021. In addition, Kearney and colleagues have developed functional-based clinical profiles of school attendance problems based on the relative strength of maintaining factors related to negative and positive reinforcement (e.g., Kearney, 2007Kearney, , 2019.…”
Section: Postmodern Dimensionsmentioning
confidence: 99%